Synthesis and optimization of bioactive silver nanobioconjugates from piper betle leaves and their active component Eugenol - R. PREETHI,; P. R. PADMA, (International Journal of Pharma and Bio Sciences, 2017)
The leaves of Piper betle (Paan), have been shown to have anticancer and antimicrobial properties due to the presence of rich bioactive components, with the most predominant being eugenol. The present study deals with the synthesis of silver nanobioconjugates from the methanolic extract of Piper betle leaves and its active compound eugenol. The presence of eugenol in the leaf extract was confirmed by HPLC analysis in the methanolic extract of betel leaves. Since various conditions influence the rapid reduction of Ag+ to Agº, different methods such as microwave heating, water bath heating at 60ºC, sunlight exposure and incubation at 37ºC were applied for the synthesis of nanobioconjugates. The antimicrobial efficiency of the synthesized silver nanobioconjugates from both leaf extract and active compound eugenol were also evaluated on Gram positive (Staphylococcus aureus) and Gram negative (Shigella flexneri) microorganisms. The results showed that the components in Piper betle leaves and active compound eugenol act as good reductants in synthesizing silver nanobioconjugates and these nanobioconjugates exhibit good antimicrobial properties.